Bilateral investment treaties 1995-2006 : trends in investment rulemaking (UN New YorkUS, 2007)
Identifies trends in the normative developments of each of the elements typically addresed in bilateral investment treaties. Traces, as well as, explains new issues that have started to be covered by recent agreements.
Keywords: INVESTMENT